2022
DOI: 10.33736/bjrst.4875.2022
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activities of Leaf Extract of Morinda elliptica

Abstract: This work was designed to evaluate the antimicrobial potential of Morinda elliptica by determining the zone of growth inhibition of the leaf extract against selected bacterial and fungal strains. Antifungal and antibacterial properties of the extract at different concentrations (25, 50, 100, 250 and 500 μg/ml) were investigated after successive maceration in four solvents in order of increasing polarity [hexane (180 g), dichloromethane (342 g), ethyl acetate (471 g), and methanol (384)]. The agar disc diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Compounds found in the species, damnacanthal and nordamnacanthal, developed active reactions against many cell lines and a high potential in developing anticancer agents (Ismail, 1999). A study on human pathogenic strains of E. coli and S. typhi showed effective results from M. elliptica leaf extract, indicating its potential in the development of new pharmaceutical products (Wakawa et al, 2022).…”
Section: Genus Morindamentioning
confidence: 99%
“…Compounds found in the species, damnacanthal and nordamnacanthal, developed active reactions against many cell lines and a high potential in developing anticancer agents (Ismail, 1999). A study on human pathogenic strains of E. coli and S. typhi showed effective results from M. elliptica leaf extract, indicating its potential in the development of new pharmaceutical products (Wakawa et al, 2022).…”
Section: Genus Morindamentioning
confidence: 99%
“…Presently, there were some studies on antibacterial activity of Morinda methanol leaf extract. When conveyed antibacterial activities of leaf methanol extract of Morinda elliptica, Wakawa et al, [3] found that at 500 µg/ml, the extract was moderately active. Mean values of the zone of growth inhibition observed against E. coli and Staphylococcus aureus was of 10.667 mm and 10.333 mm, respectively.…”
Section: Antibacterial Activity Of Methanol Leaf Extractmentioning
confidence: 99%
“…The studies showed the plant extracts were against to E. coli and S. typhii and S. aureus. The Noni extract inhibited the growth of some fungi such as A. brasiliences and A. flavus [3]. Different extracts of M. tinctoria fruits revealed antimicrobial activity against the pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, antimicrobial activity of M. elliptica leaves was reported by using agar disk diffusion method. The research showed that the extracts by n-hexane, dichloromethane, ethyl acetate, and methanol were inhibited against to E. coli and S. typhii and S. aureus and inhibited the growth of fungi A. brasiliences and A. flavus [7].…”
Section: Introductionmentioning
confidence: 99%